2013
DOI: 10.1371/journal.pone.0081871
|View full text |Cite|
|
Sign up to set email alerts
|

Incorrect Citations Give Unfair Credit to Review Authors in Ecology Journals

Abstract: The number of citations that papers receive has become significant in measuring researchers' scientific productivity, and such measurements are important when one seeks career opportunities and research funding. Skewed citation practices can thus have profound effects on academic careers. We investigated (i) how frequently authors misinterpret original information and (ii) how frequently authors inappropriately cite reviews instead of the articles upon which the reviews are based. To reach this aim, we carried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 21 publications
2
28
0
1
Order By: Relevance
“…A recurring theme within the scientometrics literature is research on citation effects of review articles (de Almeida and Guimarães 2013; Ho et al 2017;Jokic and Ball 2006;Knottnerus and Knottnerus 2009;Liu and Kuan 2016). Several authors have revealed that review articles have longer references lists (Jokic and Ball 2006), which correlates with more citations (Ioannidis et al 2016), making review articles potentially more significant than, for instance, research articles (Knottnerus and Knottnerus 2009;Teixeira et al 2013). However, while there is agreement that the review article is on average, more cited than other research items, little research has been accomplished on the differences between various citation-classes related to the different document types.…”
Section: Dealing With Review Articles In Scientometricsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recurring theme within the scientometrics literature is research on citation effects of review articles (de Almeida and Guimarães 2013; Ho et al 2017;Jokic and Ball 2006;Knottnerus and Knottnerus 2009;Liu and Kuan 2016). Several authors have revealed that review articles have longer references lists (Jokic and Ball 2006), which correlates with more citations (Ioannidis et al 2016), making review articles potentially more significant than, for instance, research articles (Knottnerus and Knottnerus 2009;Teixeira et al 2013). However, while there is agreement that the review article is on average, more cited than other research items, little research has been accomplished on the differences between various citation-classes related to the different document types.…”
Section: Dealing With Review Articles In Scientometricsmentioning
confidence: 99%
“…Although a review may not end the citation history of its included articles (Lachance et al 2014), its impact may influence the reception of primary research (Knottnerus and Knottnerus 2009). Some authors have therefore attributed review articles biasing effects on citation figures (Moed 2005;Moed and van Leeuwen 1995;Teixeira et al 2013). As an effect, it was pledged not to integrate review articles into scientometric studies (Ho et al 2017).…”
Section: Dealing With Review Articles In Scientometricsmentioning
confidence: 99%
“…The top cited publications originated from USA are explained in part by the large number of the American scientific publications [59]. There is some evidence that USA authors tend to reference articles from USA journals than from other countries [60]. Furthermore, the most highly cited articles originated from only a small number of countries.…”
Section: Authors Institutions and Countriesmentioning
confidence: 99%
“…This same study found that in the field of ecology 15% of citations falsely attributed scientific ideas to reviewers of papers, rather than to the original authors of the initial work and resultant paper [8]. Is this source of error any less likely in the health and care fields, due not least to citation laziness, using an available citation rather than following good practice of finding the original before citing it?…”
Section: Credit For Reviewersmentioning
confidence: 98%
“…In another scientific domain citation rates have been reported as having an error rate of 22% [8], and a quarter to be inappropriate in another domain [9]. There can surely be no place in health science for a measure which can be so inaccurate, nor any value in applying advanced analytic techniques to such unreliable data.…”
Section: Inaccuracymentioning
confidence: 99%